Pengembangan Indeks Wakaf: Studi Kasus Kabupaten/Kota di Provinsi Banten - Arief Fitrijanto; Bambang Juanda; Sri Mulatsih; Muhammad Findi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The implementation of regional autonomy in Indonesia is still hampered by low fiscal independence, which hinders the provision of public goods such as educational infrastructure. This study aims to develop and test the Regional Waqf Index (IWW) as an instrument to measure waqf potential at the district/city level to map alternative social financing sources. Referring to the OECD framework (2008), IWW is constructed through three dimensions: Awareness, Quantity, and Capacity. The study was conducted in eight districts/cities in Banten Province using a combination of primary data (literacy surveys) and secondary data (macroeconomic indicators). Data analysis used the Min-Max normalization method and geometric mean aggregation. The results show that the majority of areas in Banten (62.5%) are in the